SYMBOLIC STRUGGLE IN THE DISCOURSE OF THE CEASEFIRE BETWEEN HAMAS AND ISRAEL NOVEMBER 2023 - Munzila Adelawati; Habib Muharrom Sudarmawan; Vika Wafa Ilmi (Universitas Sebelas Maret, 2026)
This research examines the discourse constructed by Al Jazeera and BBC News in their coverage of the Israel-Hamas ceasefire in November 2023. Using Pierre Bourdieu’s theory of symbolic battle to identify the parties that play the role of Doxa and Hethrodoxa. While the critical discourse analysis model analysis model applied in this research is Fairclough's model, data is analyzed in three steps, namely text description, process interpretation, and explanation of socio cultural practices. The findings can be summarized as follows. First, the symbolic battle in the news discourse on the news discourse on the November 2023 Israeli and Hamas ceasefire on BBC News and Al-Jazeera have two forms, namely, (a). Introduces opposing viewspoints on Hamas and Israel with different values. (b) Rejecting viewpoints on Hamas and Issrael with different Values. Second, the symbolic battle in the discourse discourse of the November 2023 Israel and Hamas ceasefire news on BBC News and Al-Jazeera use meconnaissance strategies, namely euphemization and censorship.